H2O2‐enhanced stimulated Raman scattering of liquid water. (19th March 2019) - Li, Fabing; Wang, Ying; Li, Zhanlong; Sun, Chenglin; Men, Zhiwei
Abstract: Stimulated Raman scattering (SRS) in H2 O2 –H2 O mixture solutions are obtained in forward and backward directions. Characteristic features peaks related to OH stretching vibrations of water are the appearance of three enhancement peaks in both directions. Simultaneously, the low‐wavenumber SRS peaks in water at 840 and 1, 700 cm −1 are enhanced. The mechanism of enhancement is attributed to excess electron‐enhanced Raman scattering. The electron‐enhanced process is also discussed. Abstract : We have investigated electron‐enhanced Raman scattering of liquid water with the presence of H2 O2 . The presence of H2 O2 in mixture solutions leads to the ionization energy reduction of water molecules under strong laser irradiation, accompanying with the occurrence of avalanche ionization, generating a large number of excess electrons.